2015
DOI: 10.1105/tpc.114.135210
|View full text |Cite
|
Sign up to set email alerts
|

The Small GTPase ROP10 of Medicago truncatula Is Required for Both Tip Growth of Root Hairs and Nod Factor-Induced Root Hair Deformation

Abstract: Rhizobia preferentially enter legume root hairs via infection threads, after which root hairs undergo tip swelling, branching, and curling. However, the mechanisms underlying such root hair deformation are poorly understood. Here, we showed that a type II small GTPase, ROP10, of Medicago truncatula is localized at the plasma membrane (PM) of root hair tips to regulate root hair tip growth. Overexpression of ROP10 and a constitutively active mutant (ROP10CA) generated depolarized growth of root hairs, whereas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 68 publications
(102 reference statements)
5
43
0
1
Order By: Relevance
“…To isolate the soluble cytoplasm and insoluble membrane, the 35S: MfSTMIR ‐FLAG fusion protein was transiently expressed in N. benthamiana and extracted as described previously (Lei et al ., ). The protein concentrations from the soluble or insoluble fractions were measured using the Coomassie (Bradford) protein assay kit and were adjusted to equal concentrations.…”
Section: Methodsmentioning
confidence: 97%
“…To isolate the soluble cytoplasm and insoluble membrane, the 35S: MfSTMIR ‐FLAG fusion protein was transiently expressed in N. benthamiana and extracted as described previously (Lei et al ., ). The protein concentrations from the soluble or insoluble fractions were measured using the Coomassie (Bradford) protein assay kit and were adjusted to equal concentrations.…”
Section: Methodsmentioning
confidence: 97%
“…They can coordinate the development of epidermal and cortical cells to ensure rhizobial invasion and nodule initiation [7, 72]. Previous studies have confirmed the involvement of many nod factors in the signal transduction processes such as G-protein coupled receptor signaling pathways [73, 74], small GTPase mediated signal transduction [75, 76], calmodulin [77], Soluble N-Ethylmaleimide Sensitive Factor Attachment Protein Receptor (SNARE) proteins [58, 78] and the MAPK (Mitogen-activated protein kinase) cascade [79]. In the present study, 34 G-proteins, 18 small GTPase, 32 calmodulin and 18 SNARE proteins were present in the predicted PPIs and directly interacted with bacteria (Tables 1 and S8).…”
Section: Discussionmentioning
confidence: 99%
“…In Medicago trancatula and Lotus japonicus ROPs, MtROP10 and LjROP6 interact with the RLKs MtNFP and LjNFR5 in the membrane, respectively, and are required for rhizobium-induced nodule formation and for tip growth (Ke et al, 2012(Ke et al, , 2016Lei et al, 2015;Rivero et al, 2017). It is not known yet whether ROPGEFs colocalize with the respective ROPs and RLKs.…”
Section: Rop Function In Biotic and Abiotic Stress Responses Biotic Rmentioning
confidence: 99%